2020
DOI: 10.1002/ldr.3521
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbiotic homogenization occurred after long‐term agricultural development in desert areas across northern China

Abstract: Soil microbial communities respond significantly to long‐term agricultural development in desert areas. Because soil microbial communities are distinct in various deserts at different eco‐climate regions, their response patterns to agricultural development are diverse at a local scale. However, whether the different response patterns had some commonalities across various types of deserts at a larger spatial scale remained unclear. To address this question, historical soil samples, collected in different years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The purpose of the DM technique is to analyze the relationship between data from multiple dimensions, search for the message hidden in the data, provide decision support for scientific research, and promote the transformation of production and lifestyle. In order to understand the overall situation of soil pollution and remediation, study the mutual influence of various factors in the domain of soil remediation [ 4 ]. At the same time, synusiologic civilization construction and synusiologic environmental protection have entered a new era driven by data [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the DM technique is to analyze the relationship between data from multiple dimensions, search for the message hidden in the data, provide decision support for scientific research, and promote the transformation of production and lifestyle. In order to understand the overall situation of soil pollution and remediation, study the mutual influence of various factors in the domain of soil remediation [ 4 ]. At the same time, synusiologic civilization construction and synusiologic environmental protection have entered a new era driven by data [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, archived soils have been suggested to be useful in providing microbial ecological information (Cary and Fierer, 2014; Dolfing and Feng, 2015). Using time‐series archived soils from LTFEs across China, our recent studies found that the distribution patterns of bacterial communities corresponded to ecogeographic regions (Liu et al ., 2019) and that bacterial communities were homogenized after agricultural development in desert areas (Liu et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%